Language choice and students’ performance in mathematics and science: Evidence from Pakistan’s multilingual context - Bhutta, Sadia Muzaffar; Ansari, Aisha Naz; Ahmad, Sohail; Ali, Barkat (American Journal of STEM Education, 2026)
In Pakistan’s post‑colonial multilingual context, language in education remains sensitive and complex. Most learners use their mother tongue at home, Urdu functions as the national lingua franca, and English, an official language, serves widely as the Language of Instruction (LoI) in private schools. These overlapping roles shape classroom interaction and student performance. This paper examines how language practices in Pakistani schools, particularly consistency across textbooks, instruction, and assessment, affect achievement in science and mathematics. Findings draw on a nationally representative sample of 15,391 students and 589 teachers from 153 elementary schools, using student achievement tests and classroom observations. Students exposed to consistent language use performed significantly better than those experiencing inconsistent language use in both subjects (p